ANALYSIS OF INTERNAL CONTROL AND READINESS OF INFORMATION TECHNOLOGY ADAPTATION IN COOPERATIVES USING COBIT 5 FRAMEWORK - Tanti Widia Nurdiani; Pandu Adi Cakranegara; Stefani Lily Indarto; Vany Terisia; Muhammad Ilham Pakawaru (SEAN Institute, 2022)
Every organization must have a strong ambition to develop the application of information technology (IT) since IT application considerably assists the business processes of a company. Obviously, prior to undertaking the development of IT implementation, it is required to evaluate the company's preparedness and maturity in implementing IT-based infrastructure, human resource management, and processes. Using the Control Objectives for Information and Related Technology (COBIT 5) framework to evaluate the maturity level of IT cooperatives. The results indicated that the Maturity level value of the APO Domain from eight questions was 3.18, which is at level 3 (Defined), namely that in order to optimize the use of IT, the cooperative can make efforts to increase it, such as developing the quality of human resources in the company, building an organizational structure for IT management, procuring IT equipment based on company needs, and developing the use of IT on a regular basis. Administrative management that still relies on the Excel application must be enhanced by introducing a computerized system that makes data management simpler for cooperatives